Elementary Algebra

Published by Cengage Learning
ISBN 10: 1285194055
ISBN 13: 978-1-28519-405-9

Chapter 10 - Quadratic Equations - 10.3 - Quadratic Formula - Problem Set 10.3 - Page 453: 13



Work Step by Step

Step 1: $x^{2}-6x=0$ can also be written as $x^{2}-6x+0=0$. Comparing $x^{2}-6x+0=0$ to the standard form of a quadratic equation, $ax^{2}+bx+c=0$, we obtain: $a=1$, $b=-6$ and $c=0$ Step 2: The quadratic formula is: $x=\frac{-b \pm \sqrt {b^{2}-4ac}}{2a}$ Step 3: Substituting the values of a,b, and c in the formula, we obtain: $x=\frac{-(-6) \pm \sqrt {(-6)^{2}-4(1)(0)}}{2(1)}$ Step 4: $x=\frac{6 \pm \sqrt {36-0}}{2}$ Step 5: $x=\frac{6 \pm \sqrt {36}}{2}$ Step 6: $x=\frac{6 \pm 6}{2}$ Step 7: $x=\frac{6+6}{2}$ or $x=\frac{6-6}{2}$ Step 8: $x=\frac{12}{2}$ or $x=\frac{0}{2}$ Step 9: $x=6$ or $x=0$ Step 10: Therefore, the solution set is {$0,6$}.
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.